2018
DOI: 10.3390/socsci7080133
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experiences of Mothers of Children with the Autism Spectrum Disorders in Egypt

Abstract: The aim of this study was to gain insight into the experiences of mothers caring for children with autism spectrum disorders (ASD) in relation to the early life, resources and to address the consequences of raising a child with ASD in Egypt. Semi-structured interviews were conducted with 14 mothers of children with ASD in Egypt, the children were aged 5–14 years old (mean: 7.3 years). Data were thematically analysed. Results revealed that life with ASD was daunting for the Egyptian mothers. Findings suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 37 publications
7
62
0
13
Order By: Relevance
“…The study also confirms that parents have no choice whether to either accept or reject autistic children given by God. Thus, the results of this study confirm the results of several previous studies in which participants were Muslim, for example, a study by Gobrial (2018) in Egypt which found that mothers in Egypt believed that autistic children were blessings and gifts from God. Correspondingly, Donald (2015) argues that parents who have autistic children have no choice but to accept God's decision.…”
Section: Destiny Of Godsupporting
confidence: 89%
See 1 more Smart Citation
“…The study also confirms that parents have no choice whether to either accept or reject autistic children given by God. Thus, the results of this study confirm the results of several previous studies in which participants were Muslim, for example, a study by Gobrial (2018) in Egypt which found that mothers in Egypt believed that autistic children were blessings and gifts from God. Correspondingly, Donald (2015) argues that parents who have autistic children have no choice but to accept God's decision.…”
Section: Destiny Of Godsupporting
confidence: 89%
“…In a line with the results of previous studies, it is argued that the culture adopted by families with autistic children affects the families in terms of accepting child, making decision, or seeking treatment (Mandell & Novak, 2005;Ennis-Cole et al, 2013). Beside that the culture also will influence emotional well being and social life in the family (Pitten, 2008;Gobrial, 2018). In this regard, Malay people who are predominantly muslims cannot be separated from Islam.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the table showed that the majority of studied autism children were female and 70% of them in preparatory education level. The table (2) reflects that there is a highly satisfactory knowledge of Autism mothers regarding Autism after implementation of educational program compared with pre implementation. Also, the table shows that highly statistically significant difference of Autism definition and predisposing factors.…”
Section: Data Analysis and Findingsmentioning
confidence: 95%
“…In this study, preschool teachers' belief was divided into two: religious and general. Religious belief refers to religion and spiritual traditions that are often associated with health practices observed in cultures around the world [55]. Teachers' beliefs affect their ability in making referral decisions, as Muslim families believe that God puts an autistic child under their care not only because of fate or reincarnation but also because God wants to assess the families to see if they could take care of the child [54].…”
Section: Beliefs About Asd Among Pre-school Teachersmentioning
confidence: 99%